The neurology–psychiatry interface in epilepsy. (19th March 2021) - Murphy, Valerie; Hallahan, Brian; O' Connell, Henry; Wright, Brenda; Kelly, Brendan D; Gulati, Gautam; Shankar, Rohit
Abstract : Epilepsy and mental illness have a bidirectional association. Psychiatrists are likely to encounter epilepsy as comorbidity. Seizures may present as mental illness. Equally, the management of psychiatric conditions has the potential to destabilise epilepsy. There is a need for structured epilepsy awareness and training amongst psychiatrists. This paper outlines key considerations around diagnosis, treatment and risk while suggesting practical recommendations.